Maleficent Mirror with alexa voice services as an Internet of Things implement using Raspberry Pi 3 model b / Aida Akbar - Akbar, Aida (2018)
Maleficent Mirror is a design based on the Raspberry Pi 3 that is equipped with high technology and innovative applications and is the latest design in place of the mirror that we use today. In this era of modernization, we all been exposed to many things that lead to the development of the country and abroad.